Caylobolide B, a Macrolactone from Symplostatin 1-Producing Marine Cyanobacteria Phormidium spp. from Florida - Salvador, Lilibeth A. (2010)
A Phormidium spp. collection from Key West, Florida afforded caylobolide B (1), an analogue of the known macrolactone caylobolide A, previously isolated from a Lyngbya majuscula collection from the Bahamas. The planar structure of 1 was determined using NMR and MS experiments. The relative configuration for subunits C7–C9 and C25–C29 was assigned using Kishi's Universal NMR database. Caylobolide B (1) displayed cytotoxic activity against HT29 colorectal adenocarcinoma and HeLa cervical carcinoma cells with IC(50) values of 4.5 μM and 12.2 μM, respectively.